IMPLEMENTASI KEBIJAKAN PENGELOLAAN KAWASAN LINDUNG TERHADAP KONSERVASI SEMPADAN PANTAI DI KOTA CIREBON - Sri Wulandari (Universitas Swadaya Gunung Jati, 2013)
The problem of this research are formulated in problem statement that effectiveness of beach demarcation conservation at Cirebon Municipality has low. That problem presumed caused by implementing policy of protection area management has not effective yet.According to the problem statement mentioned above, the problem in this research identified in problem questions that :a. How much influence of implementing of protection area management against effectiveness of beach demarcation conservation at Cirebon Municipality ?b. How much influence of implementing policy of protection area management through implementing activity and organization communications, implementer agent characteristic, economic, social and politic conditions, and implementer dispositions against effectiveness of beach demarcation conservation at Cirebon Municipality ?This research done by using survey method and quantitative analysis (Path Analysis). Data collected by using interview, observation, distributing questioner to the 93 respondents, and library study.The conclusion of this research are :1. Implementing policy of protection area management has big influence against effectiveness of beach demarcation conservation at Cirebon Municipality.2. Implementing policy of protection area management through implementing activity and organization communications has small influence against effectiveness of beach demarcation conservation at Cirebon Municipality. Some weakness in implementing activity and organization communications are the less of apartus understanding, the less in communication and coordination, specific Team unavailable, and less in socialization.3. Implementing policy of protection area management through implementer agent characteristic has small influence against effectiveness of beach demarcation conservation at Cirebon Municipality. Some weaknesses in implementer agent characteristic are not at all apparatus involve in policy implementation and npt at all apparatus got a relevant training.4. Implementing policy of protection area management through economic, social and politic conditions has small influence against effectiveness of beach demarcation conservation at Cirebon Municipality. Some weakness in economic, social and politic conditions are beach society poverty, less in social culture wisdom, and less in firm against transgressor.5. Implementing policy of protection area management through implementer dispositions has small influence against effectiveness of beach demarcation conservation at Cirebon Municipality. Some weaknesses in implementer dispositions are no specific intensive, less in apparatus discipline, and less in law enforcement.